Assessment of temperament at 13 and 24 months using maternal report: validation of the Portuguese version of infant characteristics questionnaire - Carneiro, Alexandra (2017)
Temperament is a set of individual traits that has his origins in biology that is demonstrated from earlychildhood, and has some kind of continuity over time. So, and since the assessment of temperament allows us to understand further the child’s functioning, it becomes relevant validate instruments to collect this type of data. The studies presented here are part of a broader research project that aims to understand the development of children aged from 0 to 60 months. More specifically, the two studies generally aim to validate the Infant Characteristics Questionnaire (ICQ1) for 13 and 24 months of age for the Portuguese population, using mothers as informants. The first sample consists in 289 infants aged between 11 and 20months (Study 1) and the second sample comprised 398 children aged between 21 and 32 months (Study2). The two samples were collected in nurseries and day-care area of †northern Portugal, and are convenience samples. In collecting data, in addition to completing the ICQ1, the mother was asked to complete a questionnaire with demographic information about her, child and pregnancy. The specific objectives of this study were to evaluate the psychometric properties of the two versions of this instrument such as construct validity and internal consistency. The results show that factorial solutions achieved were both appropriate for these versions of ICQ1 to 13 months and to 24 months. In addition, levels of internal consistency of the dimensions obtained are generally adequate.